Primary ovarian leiomyoma in a postmenopausal woman: a case report - Sheelaa, Wills G.; Kasinathan, Ananthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian leiomyoma is a benign primary smooth muscle tumor. It is a small solid tumor commonly occurring in premenopausal women. Here we present a case of large ovarian leiomyoma in a postmenopausal woman.